Geochemical and mineralogical variations in the wallrocks of copper-bearing bodies, Namaqualand - Prins, P.(Petre) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1970.